PARTISIPASI MAHASISWA DALAM MEWUJUDKAN PEMILU BERINTEGRITAS MELALUI KEGIATAN PEMANTAUAN PARTISIPATIF DI KOTA BATAM: STUDENT PARTICIPATION IN REALIZING INTEGRITY IN ELECTIONS THROUGH PARTICIPATORY MONITORING ACTIVITIES IN BATAM CITY - Avelyn Chandra; Theodesia Lady Pratiwi; Muhammad Farhan; Nurul Hosna; Farrin Carolan (LPPM Universitas Abdurrab, 2024)
The implementation of participatory monitoring activities carried out by the Batam International University student group is a form of implementation of the community service program which aims to contribute to ensuring that all stages of the 2024 simultaneous elections held in Batam City can be held in accordance with the applicable election principles. This research uses a qualitative approach, namely through field observation methods. Through a community service program held by Batam International University in collaboration with the Election Supervisory Agency (Bawaslu) of Batam City, the implementation team succeeded in conducting participatory monitoring activities with the target of achieving the implementation of elections with integrity in Batam City, as well as ensuring the conformity between the number of voter data registered at polling stations (TPS) with data on the number of valid/invalid ballots at the time of ballot counting. The output of this activity is that all students are able to carry out monitoring activities at the polling stations (TPS) that have been determined properly, and report the results of observations in the field to the General Election Supervisory Board (Bawaslu) of Batam City through Google Form, this is done to ensure the data match on the C-Plano form uploaded through the SiRekap application with the data that has been reported by the monitoring team from Batam International University. With the implementation of this activity, it is hoped that it will be able to increase the awareness of the younger generation to care about the election process in Indonesia.